Patterns of Marketing Channel for Sangyod Muang Phatthalung Rice - Lakmuang, Suay (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
This applied research was carried out to study the marketing channels of Sangyod Muang Phatthalung rice in coordination with agricultural communities. The aim was to study both the patterns and the approaches to develop marketing channels of Sangyod Muang Phatthalung rice. Questionnaires and in-depth-interviews were used to collect data. Marketing channels included both milled rice and paddy of Sangyod Muang Phatthalung rice . The most efficient channel for paddy was distribution perfomed by farmers to the community enterprise, local traders and the rice research center. The most efficient channel for milled rice was transported by farmers of the paddy to the milling process, followed by packging before distributing it to local and non-local traders. In addition, marketing within the Small and Micro Community Enterprises was possibly developed into two ways: 1) Small and Micro Community Enterprises where certain values would be added to the Sangyod rice through a steaming process, know as steamed “ Sangyod rice”, and 2) an appropriate marketing approach. Indeed, it was found that selling the rice to Small and Micro community Enterprises was not only the most proper marketing channel but also an appropriate approach to their management ability. Because of the establishment of the Small and Micro community Enterprises, farmers get considerable interest, apart from certain common profits. Therefore, certain sustainable economy could be established within the community.